2017
DOI: 10.26803/ijlter.16.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Teachers with Dyslexia: Results of a Qualitative Study of Teachers and their Mentors

Abstract: Abstract. This study explored the perceptions of trainee teachers with dyslexia, and their mentors, of their placement experiences during their initial teacher training course. The research was conducted within one initial teacher education partnership in the north of England. Data were collected through two focus groups; one of trainees and one of mentors. Trainees described the difficulties they experienced with teaching literacy (particularly phonics), difficulties with memory and difficulties with the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…To the best knowledge of the authors, the current study is novel in focusing specifically on the everyday memory functioning of adults with dyslexia from a qualitative perspective. While differing in focus, the reports of the impact of dyslexia on memory are consistent with those identified in previous qualitative research (e.g., [32,62]) and those documented in self-report questionnaire studies (e.g., [15,21]) and (semi-)naturalistic research (e.g., [14,15]. These different sources of evidence should triangulate to inform support arrangements and reasonable adjustments.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To the best knowledge of the authors, the current study is novel in focusing specifically on the everyday memory functioning of adults with dyslexia from a qualitative perspective. While differing in focus, the reports of the impact of dyslexia on memory are consistent with those identified in previous qualitative research (e.g., [32,62]) and those documented in self-report questionnaire studies (e.g., [15,21]) and (semi-)naturalistic research (e.g., [14,15]. These different sources of evidence should triangulate to inform support arrangements and reasonable adjustments.…”
Section: Discussionsupporting
confidence: 76%
“…They also reported forgetting information under exam pressure that they otherwise knew. Difficulties with memory have also been highlighted in interviews with student teachers [62] and with acting students learning Shakespeare parts [63].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the trainees in this study acknowledged how their personal experiences of dyslexia had influenced their professional identities, referring to themselves as caring and empathetic teachers (Glazzard and Dale, 2013). Similarly, Glazzard (2018) found that when training primary school teachers, mentors acknowledged the trainees' strengths which included being skilled in teaching children with special educational needs and greater pedagogical creativity but were quick to counterbalance these strengths with weaknesses such as teaching phonics or literacy.…”
Section: Literature Reviewmentioning
confidence: 60%
“…Existing literature has explored the experiences of dyslexic primary school trainees (Morgan and Burn, 2000;Riddick, 2003;Griffiths, 2012;Glazzard and Dale, 2013;Glazzard and Dale, 2015;Glazzard, 2018). However, there is a scarcity of research into secondary school trainees where the demands, routines and subject content are vastly different; teachers will teach different age groups and a limited amount of subjects in comparison to the one class and multiple subjects taught by primary teachers (TES, 2019).…”
Section: Definition Of Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation